PENGARUH STATUS PEKERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT DANA PURNA INVESTAMA KOTA SURABAYA - Indri Dwi Apriliyani; Mochamad Mochklas; Rina Maretasari (PROCEEDING UMSURABAYA, 2022)
Human resource management as an individual manager regulates the role of the workforce of employees according to their abilities and even education in the company to produce and improve the performance of quality employees. This study aimed to determine the effect of worker status and work discipline on employee performance. There are three hypotheses tested in this study, 1. Worker Status has a negative and no significant effect on employee performance, 2. Work Discipline has a positive and significant effect on employee performance. 3. Worker Status and Work Discipline simultaneously have a positive and significant effect on employee performance. This type of research uses quantitative methods and tests hypotheses according to the data obtained from the distribution of the questionnaires to all respondents. The research population is 48 employees. This study uses saturated sampling, which is taken from the entire population. The data collection results have been processed and analyzed through SPSS version 25. The study results indicate a negative effect (-0,189) and no significant effect (0 274) on employee status on employee performance. The second shows a positive (0,467) and significant (0,000) influence on work discipline on employee performance. The third shows a positive (0,267) and significant (0,000) impact on Worker Status and Work Discipline on employee performance.Keywords: Worker Status; Work Disicipline; Employee Performance